Major Ions for Tracing Leachate Migration within Shallow Groundwater in the Vicinity of Municipal Landfill in Bantar Gebang - Bekasi - Evarista Ristin Pujiindiyati; Satrio Satrio; Rasi Prasetio (Indonesian Journal of Chemistry, 2019)
Bantar Gebang landfill located in Bekasi regency is a biggest sanitary landfill in Indonesia which comes up some refusals from local people because of its bad impact on their environment. Major ion contents in leachate and fresh groundwater were investigated during the rainy and dry season to determine contamination by leachate released from Bantar Gebang and Sumur Batu landfill. Leachate contained high concentrations of all major ions that was mainly characterized as a NaKHCO3 water type. On the other hand, most fresh groundwater samples were predominated by CaMgHCO3 and CaMgCl water type. Concentrations of K+, Ca2+, Mg2+, Na+, SO42-, Cl-, HCO3- and NO3- in leachate were to be in a maximum factor of 2110; 7; 6; 143; 20; 112; 349 and 20, respectively than its contents in groundwater. Leachate from Bantar Gebang was detected have a higher concentration than those contained in Sumur Batu that was probably due to its mature leachate. An estimated mixture of leachate to fresh water in monitoring wells (5 m and 15 m depth) was in the range of 20 to 34%, related to Na+ and Cl- signatures, while the shallow groundwater located in residents in the vicinity of these landfills exhibited maximum leachate about 2%.